A Grounded Theory of Christian Public Administrators’ Integration of Faith and Work - Christopher S. Horne (Journal of Public and Nonprofit Affairs, 2024)
About 28% of U.S. public administrators profess to be Christians who regularly attend church. Given potential impacts on public policy and services, it is important to understand how these administrators integrate faith and work. Following a constructivist grounded theory approach, this study presents a taxonomy of Christian public administrators’ faith–work integration based on analysis of 30 in-depth interviews. The taxonomy’s axes are: (1) purpose—pious versus instrumental, and (2) locus—personal, workplace relationships, or societal. All participants share faith-driven work motivation aligned with public administration values. Their mode of faith–work integration varies based on perceived religious liberty and orientations toward a sacred–secular divide versus a holistic Christian worldview. The model suggests individuals motivated by theonomic and proselytizing goals may self-select out of government service. This research offers implications for public sector leaders, educators, and Christian public administrators seeking insight into how to relate their faith and work.